Analysis of Difficulty in Understanding Mathematical Concepts Number Pattern Material for Class VIII B Students MTS Muallimin Muhammadiyah Makassar - Abdul Rahman; Gusriani; Fathrul Arriah (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2022)
The main problem in this study is the difficulty of understanding students' mathematical concepts on number pattern material in class VIII B students of MTs Muallimin Muhammadiyah Makassar. The type of research used is qualitative research with a descriptive approach involving three subjects with categories of a high, medium, and low concept understanding abilities in class VIII B MTs Muallimin Muhammadiyah Makassar. The research method used is test questions given to three subjects obtained based on recommendations from a mathematics teacher. From the results of the study, it was found that the difficulty of understanding concepts possessed by students with the category of high concept understanding is being able to complete the test questions given and fulfill three indicators of concept understanding, namely classifying objects according to their nature, applying concepts and presenting concepts in various representative forms using, utilizing and choose a particular procedure or operation. For the difficulty of understanding the medium concept with the subject of the category of medium concept understanding, it can be concluded that the subject meets two indicators of concept understanding, namely classifying objects according to their nature and being able to apply the concept the three indicators of conceptual understanding.